2005
DOI: 10.1111/j.1551-2916.2005.00229.x
|View full text |Cite
|
Sign up to set email alerts
|

Processing and Piezoelectric Properties of Lead‐Free (K,Na) (Nb,Ta) O3 Ceramics

Abstract: The preparations of (K0.5Na0.5)NbO3 (KNN)‐based ceramics were studied as lead‐free piezoelectric materials. The authors found that the addition of CuO greatly enhanced the sinterability of the KNN‐based ceramics. The sinterability and piezoelectric properties of these ceramics were dependent upon the A/B ratio, CuO doping, and the formation of a solid solution with KTaO3. Perovskite (K0.5Na0.5)xNbO3 (x=A/B ratio) was synthesized with A/B ratios of 1.00 and 1.05 by CuO doping, while (K0.5Na0.5)NbO3 contained K4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
290
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 442 publications
(296 citation statements)
references
References 39 publications
5
290
1
Order By: Relevance
“…2 These research efforts have been largely focused on ceramics based on ͑K 0.5 Na 0.5 ͒NbO 3 ͑KNN͒ and ͑Bi 1/2 Na 1/2 ͒TiO 3 ͑BNT͒, and piezoelectric coefficient d 33 values close to that of Pb-containing ceramics have been reported. [3][4][5][6][7][8][9][10][11] While d 33 is an important benchmark value in piezoelectric ceramics, it is not the decisive quantity in all applications: for actuator applications, it is often desirable to have large field-induced strain, even when the remanent polarization and correspondingly d 33 at zero field is small. We recently observed giant electric field-induced strains ͑up to 0.45%͒ in ceramics of the ͑1−x − y͒ ͑Bi 1/2 Na 1/2 ͒TiO 3 -xBaTiO 3 -y͑K 0.5 Na 0.5 ͒NbO 3 system.…”
Section: Introductionmentioning
confidence: 99%
“…2 These research efforts have been largely focused on ceramics based on ͑K 0.5 Na 0.5 ͒NbO 3 ͑KNN͒ and ͑Bi 1/2 Na 1/2 ͒TiO 3 ͑BNT͒, and piezoelectric coefficient d 33 values close to that of Pb-containing ceramics have been reported. [3][4][5][6][7][8][9][10][11] While d 33 is an important benchmark value in piezoelectric ceramics, it is not the decisive quantity in all applications: for actuator applications, it is often desirable to have large field-induced strain, even when the remanent polarization and correspondingly d 33 at zero field is small. We recently observed giant electric field-induced strains ͑up to 0.45%͒ in ceramics of the ͑1−x − y͒ ͑Bi 1/2 Na 1/2 ͒TiO 3 -xBaTiO 3 -y͑K 0.5 Na 0.5 ͒NbO 3 system.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there is a great need to develop lead-free piezoelectric ceramics with excellent piezoelectric properties for replacing the lead-containing ceramics in various applications. Several lead-free piezoelectric ceramics such as Bi 0.5 Na 0.5 TiO 3 -based materials, [1][2][3][4] Bi-layered structure materials, 5,6 tungsten bronze-type materials, 7 BaTiO 3 -based ceramics, 8 and alkaline niobatebased materials [9][10][11][12][13][14][15][16][17][18][19][20][21] have been extensively investigated. An important progress of grain-oriented alkaline niobate-based ceramics has been reported recently 22 and piezoelectric ceramics should be "lead-free at last."…”
Section: Introductionmentioning
confidence: 99%
“…It was established that Ta substitution for Nb, changes the properties of KNbO 3 and the authors also demonstrated that small amounts of Ta for Nb could enhance the piezoelectric properties of KNN ceramics [72,91]. Saito et al [92] also developed a lead-free system containing a blend of alkaline niobate (T c = 415°C) based solid solution with LiTaO 3 (T c = 615°C).…”
Section: Knbo 3 -Based Ceramicsmentioning
confidence: 99%